2020
DOI: 10.1508/cytologia.85.93
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Microdissection and Microcloning: Technique and Application in the Plant Sciences

Abstract: The technique of chromosome microdissection and microcloning, as a bridge between cytogenetics and molecular genetics, has been widely applied and play an important role in many genetic researches, such as chromosome painting probe isolation, genetic linkage map and physical map construction, and expressed sequence tags generation. To promote the further application of this technique in plants, in the present study, firstly, the experimental procedure was summarized. Secondly, the application status of this te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…This implies that the Btr-1 and Btr-2 might be more strongly conserved in the 3St and 3P chromosomes. Moreover, gene cloning may be facilitated by genome dissection during flow sorting or micro dissection (Tiwari et al 2015;Said et al 2018;Sheng et al 2020;Soares et al 2020). In this study, the chromosomes belong to the homoeologous group 3 were clearly identified.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This implies that the Btr-1 and Btr-2 might be more strongly conserved in the 3St and 3P chromosomes. Moreover, gene cloning may be facilitated by genome dissection during flow sorting or micro dissection (Tiwari et al 2015;Said et al 2018;Sheng et al 2020;Soares et al 2020). In this study, the chromosomes belong to the homoeologous group 3 were clearly identified.…”
Section: Discussionmentioning
confidence: 74%
“…Alien gene transfer by interspecific hybridization is strongly affected by chromosome collinearity (Friebe et al 1996;Qi et al 2007). Targeted gene cloning may be facilitated by capturing the syntenic chromosomes of the wild relatives, which include complex genomes, by flow sorting (Tiwari et al 2015;Said et al 2018) or even by micro dissection (Sheng et al 2020;Soares et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome specimen preparation is fundamental for several aspects of cytology, including karyotyping, fluorescence in situ hybridization (FISH), and chromosome microdissection (Bhowmick Biplab and Jha 2019, Kono et al 2019, Dash Chandan et al 2020, Nam et al 2020, Saensouk and Saensouk 2020, Samaropoulou et al 2020, Santra et al 2020, Shafiee et al 2020, Sheng et al 2020, Suto et al 2020, Widarmi et al 2020, Wang et al 2021. These techniques revealed differences in chromosome architecture between species, chromosomal abnormalities associated with diseases, and the roles of chromosomes in sex determination.…”
mentioning
confidence: 99%